Sanitation and Personal Hygiene Practices in Rural Nepal: A Case Study of Namobuddh Kavre District - Acharya, Suresh (Rural Development Journal, 2024)
Namobuddha is a Buddhist pilgrimage site located in Kavre District, Nepal. The main purpose of this study was to understand the sanitation and personal hygiene practices of people of Namobuddha, Nepal. Altogether, 80 samples have been studied through field work methods by using different tools and techniques like scheduled questionnaires interview, focused group discussion, and observation methods. Data analysis was done through MS Excels. Sanitation and personal hygiene practices are the fundamental elements for a healthy life. This research found out that every respondent was practicing basic sanitation and personal hygiene practices. Every resident of the field area is aware about the personal hygiene practices such as washing hands, washing vegetables, eating healthy foods, doing their laundry, taking bath, etc. Also, they were aware about sanitation practices such as proper toilet facility, proper disposal of wastes from kitchen and other sources, healthy drinking water, and cleaning their surroundings. Hence, overall activity of the respondents regarding sanitation and personal hygiene was satisfactory. Further, it was observed that females were more involved in sanitation and personal hygiene practices. They were involved in cooking, disposal of cooking wastages, cleaning the toilets, surrounding, washing clothes, making their children aware about unhealthy habits, etc. So, they have more knowledge on such practices and they know the consequences of unhealthy food habits and unhealthy surroundings. However, they had the problem with disposal of household wastages. Some of the households dispose of their wastes on the river due to lack of a proper disposal system. Thus, we were impressed by their awareness on sanitation and personal hygiene practice.